2020
DOI: 10.1186/s12876-020-01511-9
|View full text |Cite
|
Sign up to set email alerts
|

Linked color imaging improves visibility of reflux esophagitis

Abstract: Background With more prevalent gastroesophageal reflux disease comes increased cases of Barrett's esophagus and esophageal adenocarcinoma. Image-enhanced endoscopy using linked-color imaging (LCI) differentiates between mucosal colors. We compared LCI, white light imaging (WLI), and blue LASER imaging (BLI) in diagnosing reflux esophagitis (RE). Methods Consecutive RE patients (modified Los Angeles [LA] classification system) who underwent esophagogastroduodenoscopy using WLI, LCI, and BLI between April 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…However, recently, the use of image‐enhanced endoscopes has improved diagnostic ability. Hence, it will be necessary to prospectively evaluate the effects of both classifications on gastric cancer diagnosis in the future 14 . Sugimoto et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, the use of image‐enhanced endoscopes has improved diagnostic ability. Hence, it will be necessary to prospectively evaluate the effects of both classifications on gastric cancer diagnosis in the future 14 . Sugimoto et al .…”
Section: Discussionmentioning
confidence: 99%
“…The LCI inter-rater reliability was "moderate-substantial" for both trainees and experts for gradeM. 16 Another report indicated that detection rates for gradeM using WLI combined with LCI were higher than those using only WLI (48.9% vs. 33.0%, P < 0.001). 17 ENDOSCOPIC TREATMENT OF GASTROESOPHAGEAL REFLUX DISEASE I NOUE ET AL.…”
Section: Advances In Endoscopic Diagnosis Of Nerdmentioning
confidence: 99%
“…reported that LCI can improve the visibility of RE. 48 However, Lee et al. reported that inter‐observer agreements in diagnosing RE, including minimal changes in BLI and LCI, were not high.…”
Section: Diagnosismentioning
confidence: 99%